Stratus as a voice, guide and ambassador for emerging scientists at the University of Auckland - Hay, Debbie; Cater, John; McGillivray, Duncan (New Zealand Science Review, 2012)
​At the 2012 New Zealand Association of Scientists conference, ‘Do Emerging Scientists Have a Future in New Zealand’, Debbie Hay was given the opportunity to introduce the Stratus network, and describe the way in which it is contributing to supporting New Zealand science. Stratus is based at the University of Auckland and consists of more than two-hundred emerging researchers in the Faculties of Science, Engineering, and Medical & Health Sciences, and the related large-scale research institutes: the Auckland Bioengineering Institute and the Liggins Institute. The network consists primarily of postdoctoral researchers/research fellows and lecturers, many of whom are employed on short-duration fixed-term contracts. Stratus is independent of the University of Auckland and focuses its efforts on enhancing the research environment for early to mid-career academic staff. This article describes Stratus, its formation and how the network has evolved to date. We believe that Stratus is fulfilling an important role at the University of Auckland, and we hope that it can serve as an example for other groups of emerging researchers across New Zealand.